2018
DOI: 10.1001/jamasurg.2018.2571
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Residency and Career Dissatisfaction in Childbearing Surgical Residents

Abstract: Surgery residents who perceived stigma during pregnancy, did not have a formal institutional maternity leave policy, or altered their fellowship training plans because of challenges of childbearing expressed greater professional dissatisfaction. Mentorship in subspecialty selection and work-life integration, interventions to reduce workplace bias, and identification of obstacles to establishment of maternity leave policies are needed to enhance professional fulfillment for childbearing residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
112
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 38 publications
3
112
0
Order By: Relevance
“… 16 , 17 Without formal policies to support female surgeons during pregnancy and thereafter, they may face stigma and perceive a lack of support. 18 , 19 As such, female surgeons are more likely to delay parenthood compared to their male colleagues. 20 Recent evidence suggests that female surgeons compared with other specialties are more likely to use assisted reproduction, have a longer time to conceive and take a shorter maternity leave.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 17 Without formal policies to support female surgeons during pregnancy and thereafter, they may face stigma and perceive a lack of support. 18 , 19 As such, female surgeons are more likely to delay parenthood compared to their male colleagues. 20 Recent evidence suggests that female surgeons compared with other specialties are more likely to use assisted reproduction, have a longer time to conceive and take a shorter maternity leave.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has observed that a lack of maternity leave policies, obstacles to breastfeeding, 10 and stigma from colleagues results in a female surgeon’s increased desire to choose a less demanding specialty 24 and revisit their career choice. 19 In light of this evidence, it is clear that the dissatisfaction of female residents and faculty may deter qualified medical students from selecting a career in surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Parenting-related considerations can affect specialty and program choice as well as the training experience, including the possibility of extending the duration of training. [7][8][9][10] However, trainee perceptions about parenting challenges and resources are not completely understood. Most studies examining trainees with children focus on 1 specialty 9,[11][12][13][14][15][16] or examine 1 aspect of parenting-parental leave, [17][18][19][20] childcare, 1 or lactation.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] However, trainee perceptions about parenting challenges and resources are not completely understood. Most studies examining trainees with children focus on 1 specialty 9,[11][12][13][14][15][16] or examine 1 aspect of parenting-parental leave, [17][18][19][20] childcare, 1 or lactation. 21 Information about the needs of trainees with children across specialties is needed to inform institutional and national policies.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of specific parental leave policies has been documented across specialty training programs and is associated with career dissatisfaction in general surgery residents. 1,11,13 Further studies are warranted to elucidate the relationships between other specific support structures and resident performance and well-being.…”
Section: Discussionmentioning
confidence: 99%